Pengembangan media Janus (Jelajah Nusantara) pada mata pelajaran IPS - Utomo, Eko Prasetyo (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
This study aims to determine the process and results of the development of the Nusantara Exploration learning media on social studies subjects and to know the effectiveness of the Nusantara Exploration learning media on social studies subjects. This development research uses the development model of Dick, Carey, and Carey. Product development is tested through formative evaluation, which includes several stages: expert review of social study materials, design expert review and learning media, individual trials, small group trials, and field trials. Due diligence by the expert team obtained 97.17% results from media experts and 94.83% from material experts. After being revised based on responses from the expert team, individual trials were carried out at 85.05%, small group trials at 90.17%, and field trials at 90.47. T-test results show that in field trials, it is proven that this product is effective in improving student learning outcomes. Overall evaluation results, placing this development product in the category, is very feasible.DOI: 10.17977/um022v5i12020p028